2018
DOI: 10.15408/kauniyah.v11i2.7234
|View full text |Cite
|
Sign up to set email alerts
|

PENGUKURAN PANJANG TUBUH CACING NIPAH PENDEK Namalycastis abiuma (POLYCHAETA: NEREDIDAE) DARI PERAIRAN MANGROVE SUNGAI KAPUAS KALIMANTAN BARAT

Abstract: AbstrakCacing Nipah Pendek Namalycastis abiuma memiliki tubuh yang elastis dan mudah putus sehingga diperlukan pendekatan morfometri tubuh lain untuk menentukan panjang tubuh sesungguhnya. Tujuan penelitian ini untuk menentukan panjang tubuh total cacing nipah pendek dengan menggunakan bobot tubuh, jumlah total segmen berseta, panjang tiga segmen anterior pertama (L3) dan lebar segmen berseta atau setiger ke-10 (S-10). Spesimen yang digunakan dipilih hanya individu yang lengkap dan utuh. Pengukuran dilakukan d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
1
0
2
Order By: Relevance
“…The number of CEO images included in the company's annual statement does not indicate that the company CEO has dominant internal control, however, important CEO images are included in the annual statement to introduce the company CEO to the general public, especially stakeholders. This research is consistent with the research conducted by Aprilia (2017); Junardi et al, (2018), stated that the appearance frequency of CEO images did not significantly affect fraudulent financial statements.…”
Section: Effect Of Appearance Frequency Of Ceo Images On Fraudulent Fsupporting
confidence: 91%
See 1 more Smart Citation
“…The number of CEO images included in the company's annual statement does not indicate that the company CEO has dominant internal control, however, important CEO images are included in the annual statement to introduce the company CEO to the general public, especially stakeholders. This research is consistent with the research conducted by Aprilia (2017); Junardi et al, (2018), stated that the appearance frequency of CEO images did not significantly affect fraudulent financial statements.…”
Section: Effect Of Appearance Frequency Of Ceo Images On Fraudulent Fsupporting
confidence: 91%
“…The results showed that the directions change occurred within the company did not prove to have an effect on the level of fraudulent financial statements that occurred in the company. This research is consistent with Sihombing & Shiddiq (2014), and Junardi et al, (2018), found that capabilities proxied by the directions change had no effect on the occurrence of fraudulent financial statements.…”
Section: Effect Of Direction Change On Fraudulent Financial Statementssupporting
confidence: 90%
“…Informasi tentang cacing nipah di Kalimantan Barat sampai saat ini sebagian besar mengenai deskripsi morfologi dan maturasi N.terrestris (Chintia et al, 2020;Epriliony et al, 2021), karakteristik morfologi dan habitat N. rhodochorde , ukuran panjang tubuh N.abiuma (Junardi, 2018), sebagai informasi keberadaannya di habitat masih terbatas.…”
Section: Pendahuluanunclassified
“…Kandungan bahan organik yang tinggi pada tanah dan pelepah nipah mendukung kelangsungan hidup Namalycastis spp., yang mengonsumsi bahan organik sebagai sumber makanannya. Hal ini sejalan dengan penelitian Junardi (2018) yang mengasumsikan bahwa Namalycastis abiuma mengonsumsi bahan organik yang membusuk dari nipah. Priyandayani et al (2018) menyatakan bahwa konsentrasi karbon organik yang relatif tinggi dalam substrat akan mengundang Polychaeta untuk mencari makan.…”
Section: Bobot Cacing Nipah (Namalycastis Spp) Selama 70 Hari Inkubasiunclassified
“…The Nereidinae have several modifications to their range of specialised morphology, physiology and reproductive adaptations compared to other families of polychaetes to survive in harsh environments. This marine worm was widely spread, inhabiting the Nipa palm and mangrove sediments along the coastal swamps in Malaysia ( Junardi, 2018 ). Polychaetes have been documented for their various agricultural utilities, for example, as a medium for the degradation of vegetation, wood and roots, as a bio-indicator in a marine environment for pollution and also used as a bio-remediation of wastewater by fish and other aquafarming industries ( Dean, 2008 , Sibaja-Cordero and Echeverria-Saenz, 2015 , Tomassetti and Porrello, 2005 ).…”
Section: Introductionmentioning
confidence: 99%